Pemaknaan Menopause pada Perempuan Bangsawan Keraton Jawa - Lisy Sulistiyani; Eunike Sri Tyas Suci (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: In most cases, women experience menopause with various kind of physical and psychological symptoms. Women’s understanding on menopause is influenced by their cultural background. Royal Javanese women are not sepatared from various Javanese traditions, such as “pitutur-pitutur”, “laku Jawa”, et cetera. Such traditions are the foundation they construct menopause experience.Objective: The purpose of this research is to obtain the meaning of menopause as experienced by Royal Javanese Women.Method: A qualitative method with in-depth interview is used in this research. Informants are seven Royal Javanese Women from three Javanese palaces: Solo, Yogyakarta and Cirebon; who were selected with purposive sampling technique.Result and Discussion: Based on this research, the meaning of menopause as experienced by Royal Javanese Women is significantly influenced by their construction of Javanese culture. Menopause is understood as an important event occurred to woman’s body. As an important event, Royal Javanese Women carry out several preparations and anticipative efforts prior to Menopause. Preparations are outer and inner treatment and applied in day-to-day activities such as taking Javanese traditional herbs (jamu) and carry out Javanese traditions or rituals (fasting, meditation, et cetera).Conclusion: The Acceptance of manapausal symptoms are the result of cultural exposure and aaptation in royal live enviroments.Keywords: Menopause, Javanese Culture, Royal Javanese Women, Meaning